PENGARUH PEMBERIAN SERBUK DAUN SALAM (Syzygium polyanthum) TERHADAP KADAR FERITIN PADA TIKUS WISTAR MODEL ANEMIA - Devi, Rhisma Mutiara; Nuhriawangsa, Adi Magna Patriadi; Rahardjo, Setyo Sri (Media Penelitian dan Pengembangan Kesehatan, 2024)
Anemia is a global health problem with the prevalence of anemia in women of reproductive age ranging from 27% to 32.8%. In Indonesia, the prevalence of anemia reached 48.9% in adolescent girls, and 46.9% in pregnant women. Iron deficiency is one of the main causes of anemia, which can be triggered by inadequate nutrient intake or problems with iron absorption in the body. Bay leaves powder/BLP (Syzygium polyanthum), which are rich in iron, have not been fully utilized in anemia treatment. The study aimed to analyze BLP administration on ferritin levels in female Wistar rats with anemia. Ferritin research with a Pre and Post Control Group experimental design was conducted at LPPT UGM and UPT UNS for 45 days (August–October 2023). Female white rats (Rattus norvegicus strain Wistar) aged 6 weeks with weight range of ±100–200 g were obtained from UD Wistar Yogyakarta. During acclimatization, they were given comfeed and AIN-93M diets without iron. Anemia in rats was induced by a low-iron diet for 15 days before treatment. BLP was administered for 28 days with different doses of bay leaf powder (3 dose groups) P1 18,6mg/200gr BB, P2 36 mg/200grBB, P3 55,6 mg/200grBB. Ferritin were obtained by taking blood from mice to obtain blood serum using the centrifuge method.  Group P3 (SDS 55.6mg/100BB), there was a significant change in ferritin during the treatment. The study concluded was an influence of administering SDS at a dose of 55.6 mg/100BB on changes in ferritin in the anemia rat model.